Porous Janus materials with unique asymmetries and functionality. (December 2021) - Yan, Linlin; Yang, Xiaobin; Zhang, Yanqiu; Wu, Yadong; Cheng, Zhongjun; Darling, Seth B.; Shao, Lu
Graphical abstract: A summary of the properties, functions, and potential applications of porous Janus materials based on various asymmetries (e.g. wettability, charge, pore size or structure, thermal or electrical conductivity, or chemical activity). Abstract: Porous Janus materials have attracted widespread attention due to their asymmetry in wettability, charge, pore size or structure, thermal/electrical conductivity, and chemical activity. Multifunction integration and unique directional manipulation of liquid, ion, or gas within porous Janus materials enable rapid progress in diverse applications such as fog collection, personal moisture and healthcare management, energy conversion, water purification, sensor devices, and biomedical applications. Compared with conventional homogeneous materials, porous Janus materials not only showcase superior performance and energetic potential but also open up new applications by virtue of the synergistic or independent effects of asymmetry. This comprehensive review systematically analyzes the research progress of porous Janus materials, highlighting fabrication strategies, synergistic/independent work mechanisms, and emerging advanced applications. Finally, ongoing challenges and outlook for the future research of porous Janus materials are presented.